Cover Image. (June 2018) - Minagi, Y.; Ono, T.; Hori, K.; Fujiwara, S.; Tokuda, Y.; Murakami, K.; Maeda, Y.; Sakoda, S.; Yokoe, M.; Mihara, M.; Mochizuki, H.
Abstract : The cover image, by Y. Minagi et al ., is based on the Original Article Relationships between dysphagia and tongue pressure during swallowing in Parkinson's disease patients, DOI:10.1111/joor.12626 .